2009
DOI: 10.1007/s11738-009-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Cu,Zn-superoxide dismutase is differently regulated by cadmium and lead in roots of soybean seedlings

Abstract: The cadmium (Cd 2? ) and lead (Pb 2? )-induced changes in Cu,Zn-SOD gene expression on the level of mRNA accumulation and enzyme activity were analyzed in roots of soybean (Glycine max) seedlings. The Cd 2? caused the induction of copper-zinc superoxide dismutase (Cu,Zn-SOD) mRNA accumulation, at each analyzed metal concentration (5-25 mg/l), whereas in Pb 2? -treated roots this effect was observed only at the medium metal concentrations (50-100 mg/l of Pb 2? ). The analysis of Cu,Zn-SOD activity proved an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…The antioxidant systems can be induced both at enzyme and gene levels under Cd stress. Pawlak et al (2009) reported that copper-zinc superoxide dismutase (Cu, Zn-SOD) mRNA accumulation in roots was induced in soybean (Glycine max) seedlings subjected to 5-25 mg L -1 Cd. Tzure-Meng et al (2009) indicated that induction in the activities of FeSOD, APX, and GR occurred in the marine macroalga Ulva fasciata to prevent the occurrence of oxidative damage under Cd stress.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant systems can be induced both at enzyme and gene levels under Cd stress. Pawlak et al (2009) reported that copper-zinc superoxide dismutase (Cu, Zn-SOD) mRNA accumulation in roots was induced in soybean (Glycine max) seedlings subjected to 5-25 mg L -1 Cd. Tzure-Meng et al (2009) indicated that induction in the activities of FeSOD, APX, and GR occurred in the marine macroalga Ulva fasciata to prevent the occurrence of oxidative damage under Cd stress.…”
Section: Introductionmentioning
confidence: 99%
“…The Cd induced copper-zinc superoxide dismutase (Cu, Zn-SOD) mRNA accumulation in roots of soybean (Glycine max) seedlings exposed to 5-25 mg l -1 of Cd concentration (Pawlak et al 2009). Daghan et al (2010) observed that the ScMTII gene bearing transgenic tobacco plant accumulated 19.8% higher Cd than the nontransgenic tobacco plant.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitor testing revealed that α.1 belonged to Mn‐SOD, and all of the β and γ SOD isoenzymes belonged to Cu/Zn‐SOD. According to previous studies, no activity of Fe‐SOD was detected in the normal soybean roots and leaves . However, three Fe‐SOD isoenzymes (I, II and III) were induced by higher Cd 2+ , while the effect of Pb 2+ on Fe‐SOD was different from that of Cd 2+ .…”
Section: Discussionmentioning
confidence: 87%
“…Heavy metals may act on the expression of Cu/Zn‐SOD in plants . For example, accumulation of Cu/Zn‐SOD mRNA was induced by Cd 2+ and Pb 2+ in roots of soybean seedlings . In addition, the activity of Cu/Zn‐SOD was upregulated in the presence of Cd 2+ /Pb 2+ stresses.…”
Section: Introductionmentioning
confidence: 99%